Analyze of Employe’s Motivation Factor in Sekretariat Daerah in Kabupaten Bengkulu Utara - Marsidi Marsidi; Askani Askani (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to describe the work motivation of employees at the Regional Secretariat of North Bengkulu Regency. the number of respondents/informants which includes Head of Division 2 people, Head of Subsection 10 people and Staff 13 people. The data method was carried out by interviews and questionnaires, the method of data analysis was descriptive qualitative. The research uses based on research results, the most important motivational factor is the need for prestige and actually what makes an employee feel confident to do a job / work of a business, which has been done by the employer to motivate. Employees have good communication with appropriate words.